2013
DOI: 10.1038/nn.3333
|View full text |Cite
|
Sign up to set email alerts
|

EGF transactivation of Trk receptors regulates the migration of newborn cortical neurons

Abstract: The development of neuronal networks in the neocortex depends on control mechanisms for mitosis and migration that allow newborn neurons to find their accurate position. Multiple mitogens, neurotrophic factors, guidance molecules and their corresponding receptors are involved in this process, but the mechanisms by which these signals are integrated are only poorly understood. We found that TrkB and TrkC, the receptors for brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3), are activated by epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 53 publications
7
87
0
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) has been widely implicated in the development, migration, differentiation and survival of fetal neurons (1). BDNF binds its conjugate receptor, TrkB, and initiates a signaling cascade marked by increased activity of the pi3K/Akt growth pathway leading to production of pro-migratory, antiapoptotic and pro-survival proteins (2,3).…”
Section: Abstract Neurotrophins Are a Family Of Growth Factors Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain-derived neurotrophic factor (BDNF) has been widely implicated in the development, migration, differentiation and survival of fetal neurons (1). BDNF binds its conjugate receptor, TrkB, and initiates a signaling cascade marked by increased activity of the pi3K/Akt growth pathway leading to production of pro-migratory, antiapoptotic and pro-survival proteins (2,3).…”
Section: Abstract Neurotrophins Are a Family Of Growth Factors Thatmentioning
confidence: 99%
“…BDNF binds its conjugate receptor, TrkB, and initiates a signaling cascade marked by increased activity of the pi3K/Akt growth pathway leading to production of pro-migratory, antiapoptotic and pro-survival proteins (2,3). it has been uniquely demonstrated that activation of the BDNF signaling pathway transactivates the epidermal growth factor receptor (EGFR) even in the absence of the endogenous EGF ligand (1). As a consequence, this augments the activity of phospholipase-c-y (pLcy) and of downstream targets such as various protein kinase c isoforms.…”
Section: Abstract Neurotrophins Are a Family Of Growth Factors Thatmentioning
confidence: 99%
“…Another possibility is that the receptors for Ntf3 (Trks) are also activated by alternate pathways in the developing cortex (Lee et al, 2002). For example, recent work has shown that EGFR can transactivate both TrkB and TrkC (Ernfors et al, 1994;Puehringer et al, 2013). Interestingly, Bdnf and Ntf3 have opposing functions in laminar fate specification (Fukumitsu et al, 2006).…”
Section: Ntf3 Promotes Ul Neurogenesis At the Expense Of DL Neuronsmentioning
confidence: 99%
“…Also, there is increasing evidence of TrkB activation in a manner that is independent of neurotrophins. Thus, a recent study reported that cortical development requires neurotrophin-independent TrkB transactivation (Puehringer et al 2013).…”
Section: (D) Trkbmentioning
confidence: 99%